Influence of Type of Farm Input Subsidies on Maize Production in Trans Nzoia West Sub County, Trans Nzoia County, Kenya - Wafula, Barasa Protus; Nyantika, Dr. Daniel; Ekisa, Dr. Tom George; Mabaya, Dr. Mamboleo Denis (International Journal of Current Innovations in Advanced Research, 2023)
Food security all over the world is the biggest challenge affecting humanity; the problem is even more serious among the low-income and food shortage nations. In order to achieve reasonably high food produce to deal with this situation, sustainable strategies are required. One of such strategies is what this Study wished to address. Hence, the Study made an endeavour to find out the challenges of farm inputs subsidies on maize production in Trans Nzoia West Sub County, Trans- Nzoia County, Kenya. The study was of significance to stakeholders in the Agriculture sector ranging from The National Ministry of Agriculture and the County; agricultural staff implementing the project and the farmers. The study was based on Social Protection Theory. A descriptive survey design was used since the study was both qualitative and quantitative in nature. A sample of 160 was selected from a target population of 1510 for data collection. Questionnaire and an interview schedule were used as tools of primary data collection. Data instruments were pretested in Trans-Nzoia East Sub County to test their reliability and viability. Data was collected, coded and analyzed using Statistical Package for Social Sciences (SPSS) version 20.0 findings showed that there was a significant effect of subsidized seed given that majority of the farmers produced bags using certified seed. It was recommended that the government should appoint distribution points where input subsidies should be channeled through location Agriculture Officers’ rather than the National Cereals and Produce Board.